2021
DOI: 10.1155/2021/6628272
|View full text |Cite
|
Sign up to set email alerts
|

Stability Mechanism and Control Factors on Equipment Removal Area under “Goaf‐Roof‐Coal” Structure

Abstract: One of the main difficulties in longwall mining (LM) is the movement of mining equipment from one panel to the next panel during mining process. The shields of the LM face may be damaged by the collapse of the roof in shallow coal seam under the “Goaf-Roof-Coal” (GRC) structure, especially when moving the shields from the current panel to the next panel. In order to solve this problem, the stability mechanism and its control factors during the LM equipment removal were investigated by using comprehensive metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…In view of the complex fault structure and the difficulty of roof management during the late mining period of the working face, Song [13] selected a reasonable position of the stopping line through the study of roof transport law and analysis of mine pressure measurements. Through numerical simulation, Chen et al [14] concluded that there are four different damage zones around the stopping space, namely the shear damage zone, tensile damage zone, partial elasticity zone, and plastic damage zone, and adopted various measures such as optimizing the position of the stopping line, reducing the width of the stopping section, and increasing the number of anchor cables to ensure the stability of the surrounding rock in the stopping space. Wu et al [15] proposed a rapid withdrawal technology for nonpre-driven retraction channels in heavily mechanized top-coal caving faces by studying the law of mine pressure appearing on the working face and the reasonable position of stopping lines for the problem of crushed pre-driven retraction channels.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the complex fault structure and the difficulty of roof management during the late mining period of the working face, Song [13] selected a reasonable position of the stopping line through the study of roof transport law and analysis of mine pressure measurements. Through numerical simulation, Chen et al [14] concluded that there are four different damage zones around the stopping space, namely the shear damage zone, tensile damage zone, partial elasticity zone, and plastic damage zone, and adopted various measures such as optimizing the position of the stopping line, reducing the width of the stopping section, and increasing the number of anchor cables to ensure the stability of the surrounding rock in the stopping space. Wu et al [15] proposed a rapid withdrawal technology for nonpre-driven retraction channels in heavily mechanized top-coal caving faces by studying the law of mine pressure appearing on the working face and the reasonable position of stopping lines for the problem of crushed pre-driven retraction channels.…”
Section: Introductionmentioning
confidence: 99%
“…e retracement channel connected with the working face needs to be set in the stopping line for the retracement of working face equipment, which is different from normal mining. e characteristics of large sections, equipment, complex technology, and close proximity to the rear gob determine that only by reasonably setting and supporting the retracement channel, the working face equipment can be safely and quickly retraced [2]. In the working face of a thin coal seam with a soft roof, the soft roof easily causes roof falling (leakage) and support failure in the retracement space because of the low mining height.…”
Section: Introductionmentioning
confidence: 99%